Identification of an endosomal antigen specific to absorptive cells of suckling rat ileum (The Rockefeller University Press, 1987)
A membrane fraction enriched in apical endosomal tubules was isolated from absorptive cells of suckling rat ileum and used as an immunogen to generate anti-endosome monoclonal antibodies. By immunofluorescence, one of these antibodies bound exclusively to the region of the apical endocytic complex in ileal absorptive cells, but not to other cell types. Immunoblot analysis showed the antigen as a diffuse 55-61-kD band which was highly enriched in the endosome fraction over whole-cell homogenate. The antigen appears to be an intramembrane glycoprotein: it partitioned primarily in the detergent phase after TX-114 extraction, and shifted to 44 kD after chemical deglycosylation. EM immunocytochemistry showed that the antibody bound to the luminal side of endosomal tubule membranes, a portion of endosomal vesicle membranes, and in endocytic pits of apical plasma membranes. However, it did not bind to multivesicular bodies, the giant lysosome, or other organelles. Immunocytochemistry after uptake with adsorbed or soluble tracer proteins showed that the antigen labeled portions of both prelysosomal pathways previously described in these cells (Gonnella, P.A., and M. R. Neutra, 1984, J. Cell Biol., 99:909-917). The function of this glycoprotein is not known, but inasmuch as it has been detected only in absorptive cells of suckling rat ileum, it may serve a function specific to these cells. Nevertheless, this endosomal antigen, designated glycoprotein (gp) 55-61, will serve as a useful marker for exploring membrane dynamics in early stages of the endocytic pathway.